Physical and mechanical properties of jabon wood particleboards were studied. The wood particle from lower, upper parts of trunk and branches of jabon tree were used. The wood wettability was observed at lower, upper part of trunk and branches of 2.5 years old jabon tree from Cihideung Ilir village, Bogor. The quality of particleboard in terms of density, moisture content, thickness swelling, modulus of elasticity, modulus of rupture, internal bond, and screw holding power were tested accordance - Surdiding RUHENDI; Erwinsyah PUTRA (Departemen Hasil Hutan, IPB, 2011)
Physical and mechanical properties of jabon wood particleboards were studied. The wood particle from lower, upper parts of trunk and branches of jabon tree were used. The wood wettability was observed at lower, upper part of trunk and branches of 2.5 years old jabon tree from Cihideung Ilir village, Bogor. The quality of particleboard in terms of density, moisture content, thickness swelling, modulus of elasticity, modulus of rupture, internal bond, and screw holding power were tested accordance with JIS 5908:2003. In general partikel bord made of jabon wood from upper, lower of trunk and branches of jabon were as follow: density (0.61 g/cm³, 0.58 g/cm³, 0.65 g/cm³), moisture content (9.9%, 9.7%, 9.3%), thickness swelling (44.8%; 52.3%; 30.6%), modulus of elasticity (9716.1 kg/cm², 7997.4 kg/cm², 12954.3 kg/cm²), modulus of rupture (82.6 kg/cm², 71.3 kg/cm², 90.8 kg/cm²), internal bond (5.06 kg/cm², 3.02 kg/cm², 6.12 kg/cm²) and screw holding power (30.6 kg/cm², 38.8 kg/cm², 47.5 kg/cm²), respectively. The quality of jabon wood were not affected by the precentage of adhesive used. There were a variability in wettability of jabon wood between parts of tree. The wettability of jabon wood of upper, lower trunk and branches were 1800.4, 2126.1 and 2169.7 mm, respectively. Furthermore, the variabilities were also happened in almost all physical dan mechanical properties of the particleboard. The higher the wettability the higher the quality of the particleboard, means that wettability as a good indicator for quality of jabon woods particleboard.The quality of particleboard made of woods from branches were better than others. Keywords: particleboard, jabon, wettability,gluability